Mycotoxin: Its Effect on Animal Health and its Residues in Animal Products and its Control - Widiastuti, Raphaella (Indonesian Animal Sciences Society, 2006)
Mycotoxins are the toxic metabolites of certain fungi which is able to influence animal health . Five types of the most important mycotoxins are aflatox ns, ochratoksin A . zearalenone, trichotecenes and fumonisin . The effect of mycotoxin on animal health depends on the type and amount of the mycotoxins consumed . The occurrence of mycotoxin causes animal health problem and also leads to the arise of mycotoxin residues in food derived from animal products such as meat, eggs and milk which causes human health problem . Controlling the occurrence of mycotoxins in animal feed and food products through some treatments and prevention is important to avoid further negative effects of mycotoxins . Key words : Mycotoxins, animal health, residue, control